Surface‐confined guanidinium ionic liquid as a new type of stationary phase for hydrophilic interaction liquid chromatography. Issue 18 (30th July 2021) - Qiao, Lizhen; Sun, Ruiting; Tao, Yuan; Yu, Chunmei; Yan, Yang
Abstract: Guanidinium‐based ionic liquids possess lower toxicity and greater designability than commonly used species and have presented good performances in liquid‐phase extraction and stationary phase for capillary gas chromatography. In the present work, a novel type of surface‐confined guanidinium ionic liquid stationary phase was developed by bonding a hexaalkylguanidinium ionic liquid N, N, N', N' ‐tetramethyl‐ N", N"‐ diallylguanidinium bromide onto the surface of 3‐mercaptopropyl modified silica. The obtained surface‐confined guanidinium ionic liquid silica materials were characterized by elemental analysis, infrared spectroscopy and thermogravimetric analysis, and then packed as a high‐performance liquid chromatography column for the evaluation of chromatographic retention behavior. Typical polar compounds were used to evaluate the separation performances, and the changes of retention with water content in mobile phase further suggested the hydrophilic interaction liquid chromatography retention mechanism. Moreover, the effect of different chromatographic factors (salt concentration, mobile phase pH, and column temperature) on retention was investigated with a series of compounds as test solutes to gain insights into the retention mechanism. The results indicated that the surface‐confined guanidinium ionic liquid stationary phase exhibited a hydrophilic interaction liquid chromatography/anion‐exchange mixed‐mode retention behavior and possessed promising potential in separating a wide range of compounds as an alternative stationary phase for high‐performance liquid chromatography.